Trapping Technique for Successful Retrieval of a Ruptured Balloon Catheter Entrapped in Coronary Artery : A Case Report - Putri Annisa Kamila; Budi Satrijo; Mohammad Saifur Rohman; Heny Martini; Indra Prasetya (Universitas Brawijaya, 2020)
Introduction: Device entrapment during PCI is an uncommon complication with incidence of less than 1%. Percutaneous retrieval should be favored as the treatment of choice for this condition.Case Illustration: A 61-year-old patient came for an elective percutaneous coronary intervention (PCI) procedure. She suffered from chest pain while doing moderate activities for 1 month. Angiography showed a diffuse lesion with maximum stenosis 90% in the proximal LAD, stenosis 75% in the proximal of Left Circumflex Artery (LCx), and diffuse lesions in the proximal and mid of the Right Coronary Artery (RCA). We decided to perform PCI in the LAD. A transfemoral coronary intervention was performed using a Judkins Left 3.5 (7F) guiding catheter to engage the LAD. A Guidewire ( Run-through NS Floppy) was advanced to the distal LAD. Balloon angioplasty was performed with a 2.75 x 15 mm Fluydo balloon in the proximal LAD at 16 bars, but the balloon was entrapped and while withdrawing the balloon, it accidentally ruptured in the LAD artery with the remaining segment inside the guiding catheter. A second Run-through NS Floppy Guidewire was inserted across the ruptured balloon and a 2.5 x 20 mm Fluydo Balloon was passed on the second wire and was inflated at 16 atm pressure, inside the guiding catheter, trapping the ruptured balloon. The ruptured balloon was successfully removed, by withdrawing the whole system, including the guiding catheter and the wire. Finally, we re-engaged the LAD with the same guiding catheter, passed the wire, and post dilated the stent on the LAD to achieve a good result.Conclusion: Percutaneous retrieval using trapping technique could represent a safe and effective technique for ruptured and entrapment of a balloon-catheter in a coronary artery.